An Analytical Exploration of Mobile Virtual Social Networks and Their Impact on Teenagers\' Academic Quality of Life - Amrollah Amani Kalarijani; Mahsa Talebi; Bita Erfani (Iranian Journal of Educational Research)
Objective: Due to the fact that students spend a very high proportion of their life time in school, therefore, evaluating the quality of their life in school and the role of effective factors in it is of great importance; Therefore, the present study was conducted with the aim of investigating the effect of the use of mobile virtual social networks on the quality of academic life of teenagers. Methods: The methodological approach utilized was descriptive in nature and of a correlational type. The target demographic encompassed all tenth-grade male and female students from two districts in Baharestan during the academic year of 2023, with a total of 100 eligible individuals who willingly opted to participate in the study; the instruments employed for data collection included questionnaires pertaining to the utilization of mobile virtual social networks as developed by Javadinia et al. (2011) and the assessment of quality of life in educational settings as conceptualized by Ainley and Bourke (1992). For the purpose of data analysis, Pearson's correlation coefficient and multiple regression analysis were applied utilizing SPSS-22 software. Results: The findings revealed that there exists a significant and negative correlation between the usage of mobile virtual social networks and the quality of academic life, indicating that mobile virtual social networks serve as a negative predictor of students' academic quality of life. Conclusions: In conclusion, the study emphasizes the need for greater awareness of the effects of mobile virtual social networks on students' academic well-being.